Workshop on Scientific Paper Writing for Teachers Classroom Action Research Approach at Madrasah Aliyah Laboratorium Jambi - Taridi, Muhamad; Muslimahayati, Muslimahayati; Fitriani, Suci; Chaniago, Fransisiko; Ramdayeni Sakunti, Sri; Summiyani, Summiyani; Afifah, Yuliana; Hamdan, Hamdan (Lembaga Dongan Dosen, 2024)
Classroom Action Research (CAR) plays a crucial role as a benchmark in improving teacher professionalism. Through the implementation of CAR, it is expected that teachers can identify elements that can be applied to enhance the quality of the learning process, ultimately contributing to the improvement of the national education quality. This community service research method applies the ABCD approach. The purpose of this activity is to provide scientific paper writing training on CAR for teachers. The expected outcomes of this activity are, first, the teachers' ability to understand and master the formulation of CAR, and second, the teachers' ability to conduct Classroom Action Research. The implementation of this activity is expected to enhance the knowledge and skills of training participants in creating scientific works on CAR, especially in formulating Classroom Action Research proposals. Additionally, participants are expected to be able to compose CAR papers in accordance with the procedures conveyed during the training.